Monitoring Forest Cover Loss Due to The Impact of Mining Activities Using Google Earth Engine in West Aceh Regency - Hani, Fajrul; Sandriadi, Wahyu; Farhan, Muhammad; Nanda, Muhammad; Alhafsi, Muhammad Arfan; Sugiyanto*, Didik (Aceh International Journal of Science and Technology, 2025)
In recent years, forest areas in Aceh Province, especially in West Aceh Regency, have experienced a significant decline in forest cover. This can negatively impact biodiversity, community quality of life, and natural disaster risk, exacerbating global climate change. The fact that West Aceh is one of the regencies with the highest number of gold and coal mining companies in Aceh is a significant concern when assessing whether mining activities impact forest cover loss. This study aims to monitor and quantify forest cover change and the impact of mining activities in Aceh Barat from 2019 to 2024. The research methodology included the use of Google Earth Engine (GEE) for Sentinel-2 satellite image analysis by calculating the Normalized Difference Vegetation Index (NDVI); NDVI values above 0.7 were classified as forest, values below 0.7 as non-forest, and negative values as water bodies. The analysis showed that forest cover loss in West Aceh reached 13030.84 ha over the last five years at an average rate of 2606.17 ha/year. Illegal gold mining activities contributed 12.8%, legal coal mining 10.2%, and legal gold mining 7.3% to forest cover loss, while non-mining factors caused 69.7%. This study presents a cost-effective forest monitoring method that supports biodiversity protection and improved forest management policies in mining areas.